2018
DOI: 10.1016/j.jdermsci.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode 585 nm photomodulation inhibiting melanin synthesis and inducing autophagy in human melanocytes

Abstract: Our finding demonstrated that LED photomodulation with 585nm wavelength suppressed melanin content in HEMs, and the effect was caused by its dose-dependent inhibition on melanogenesis and the induction of HEMs autophagy. This may provide new insights into the efficacy of LED photomodulation in the treatment of hyperpigmentation disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…Upon undergoing UV exposure, melanocytes can undergo photosensitization by generating superoxide radicals in cells ( 97 ). In addition, p62 is upregulated upon phototherapy (UVA radiation and light-emitting ode 585 nm) in the melanocyte ( 61 , 62 ). Melanin confers protection from UV-induced DNA damage, maintains skin homeostasis, modulates the immune environment, and regulates skin color by autophagy ( 56 , 63 65 ).…”
Section: Autophagy In Skin Immune Cellsmentioning
confidence: 99%
“…Upon undergoing UV exposure, melanocytes can undergo photosensitization by generating superoxide radicals in cells ( 97 ). In addition, p62 is upregulated upon phototherapy (UVA radiation and light-emitting ode 585 nm) in the melanocyte ( 61 , 62 ). Melanin confers protection from UV-induced DNA damage, maintains skin homeostasis, modulates the immune environment, and regulates skin color by autophagy ( 56 , 63 65 ).…”
Section: Autophagy In Skin Immune Cellsmentioning
confidence: 99%
“…Primary NHEK, NHEM, and dermal fibroblast cultures were performed as described previously (Chen et al, 2018) and were cultured under standard conditions in Medium 254 supplemented with human melanocyte growth factors (Invitrogen, Carlsbad, CA), keratinocyte-defined serum-free medium supplemented with human keratinocyte growth factors (Invitrogen), or DMEM (Invitrogen) medium supplemented with 10% fetal bovine serum (volume/volume). NHEKs, NHEMs, and human fibroblasts were fed every 2e3 days, and further passaged at 1:2 when they became 80% confluent, with experiments being carried out from 2 to 3 passages.…”
Section: Cell Culturementioning
confidence: 99%
“…61 LED photo modulation at a 585 nm wavelength reduces the melanin content of inhuman epidermal melanocytes (HEMs), via dose-dependent inhibition of melanogenesis and induction of HEM autophagy. 62 It has been shown that β-mangostin from seedcases of Garcinia mangostana control α-MSH-mediated melanogenesis by inhibiting autophagy, which clearly recovers the premelanosome protein and tyrosinase degraded in B16F10 melanoma cells and a 3-dimensional human skin model. 2 Tranexamic acid (TXA) has been frequently used to decrease melanin synthesis in patients with melisma and as a raw material for functional whitening cosmetics.…”
Section: Current Mechanisms For Inhibiting Melanin Productionmentioning
confidence: 99%